2019
DOI: 10.1093/jjco/hyz116
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcomes after open radical prostatectomy, laparoscopic radical prostatectomy and permanent prostate brachytherapy

Abstract: Objective To assess patient-reported outcomes after open radical prostatectomy, laparoscopic radical prostatectomy and permanent prostate brachytherapy. Methods patient-reported outcomes were evaluated using Expanded Prostate Cancer Index Composite scores at baseline and 1, 3, 6, 12 and 36 months after treatment, respectively, using differences from baseline scores. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…In the present study, bowel QOL deteriorated more in patients who underwent LDR‐BT versus RARP. This result is consistent with those of other reports 3,12,19 . Blanchard et al 3 reported that LDR‐BT alone worsened bowel QOL compared with nerve‐sparing RARP.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, bowel QOL deteriorated more in patients who underwent LDR‐BT versus RARP. This result is consistent with those of other reports 3,12,19 . Blanchard et al 3 reported that LDR‐BT alone worsened bowel QOL compared with nerve‐sparing RARP.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, sexual QOL was significantly worsened in the RARP group versus the LDR‐BT group. The deterioration of sexual QOL caused by LDR‐BT and radical prostatectomy has been reported in other studies 3,19,20,23 . Mullins et al 24 reported that patients treated with radical prostatectomy with or without nerve sparing had worsened sexual QOL compared with those who underwent brachytherapy.…”
Section: Discussionmentioning
confidence: 66%
“…The treatment options are multifaceted and include prostatectomy, radiation therapy, hormonal therapy, chemotherapy, or a combination of these [ 5 – 7 ]. While a whole-gland treatment approach shows good oncological results, it may also have life-altering side effects such as incontinence, impotence, and infection [ 8 ]. As the majority of PC are localized within the prostate gland [ 9 ], minimal invasive local treatment approaches have been gaining in interest and popularity as the adverse events reported are low while having good oncological outcome [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…found that physician ratings of symptoms do not correlate well with PROs, and that disagreement between physician and patient ratings did not decrease over time. [ 5 ] We have reported PROs for ORP compared to LRP,[ 6 , 7 ] with the finding that ORP was better for urinary incontinence. However, we have not examined the outcomes of RARP, and there are few reports on this surgery using PROs in Japan.…”
Section: Introductionmentioning
confidence: 99%